2003
DOI: 10.1080/744816685
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Solvatochromism of Dyes in Liquid Crystals

Abstract: Citation for published item: ¦ lssonD vF yF nd zlewskiD wrek nd oertsD eF nd wsutniD eF nd voveD qF hF nd grossD qF rF nd floorD hF nd uyD eF tF nd oolhouseD eF hF nd wsutniD eF nd sudD eF @PHHQA 9yrienttion nd solvtohromism of dyes in liquid rystlsF9D woleulr rystls nd liquid rystlsFD RHP @IAF ppF RQESQF Further information on publisher's website: httpXGGdxFdoiForgGIHFIHVHGURRVITTVS Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…[4]). This observation is also consistent with our previous study [12]. It is notable that the shift in the absorption maxima is larger than that of the emission maxima relative to the viscous solvents DEG and glycerol.…”
Section: Solvatochromismsupporting
confidence: 93%
See 4 more Smart Citations
“…[4]). This observation is also consistent with our previous study [12]. It is notable that the shift in the absorption maxima is larger than that of the emission maxima relative to the viscous solvents DEG and glycerol.…”
Section: Solvatochromismsupporting
confidence: 93%
“…Hosts employed were LCs and isotropic solvents for which previous studies had indicated the formation of H-bonds with these dyes [12]. These measurements confirmed that the spectral shifts of the chromophores in the LC are much larger than those in isotropic solvents of varying polarity and hydrogen bonding ability.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations